1994
DOI: 10.1177/019262339402200309
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Glomerular Anionic Sites in Canine Anti-Glomerular Basement Membrane Nephritis with Onset of Severe Proteinuria

Abstract: Rabbit anti-glomerular basement membrane serum (AGBM) or normal rabbit serum (NRS) were given intravenously (2 ml/kg body weight) to 8 male beagle dogs. Light and transmission electron microscopy and immunofluorescence were performed on the kidneys on day 7 postinjection. Alterations of anionic sites (ASs) of glomerular basement membrane (GBM) in peripheral, proximal, and paramesangial portions were studied quantitatively by electron microscopy using polyethyleneimine (PEI; molecular weight = 1,800) as a catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…in animal models of diabetes with known proteinuria (Chakrabarti et al, 1989;Moriya et al, 1993;Sugimoto et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…in animal models of diabetes with known proteinuria (Chakrabarti et al, 1989;Moriya et al, 1993;Sugimoto et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Four animals were assigned to each group. Staining of glomerular anionic sites with polyethyleneimine (PEI; molecular weight = 1,800; Wako Pure Chemical Industries, Ltd., Osaka) was performed by a minor modification of the method described by Schurer et al [13] and Sugimoto et al [14]. Freshly sampled renal cortex was cut into 0.5 mm 3 pieces and immersed in 0.5% PEI in physiological saline for 30 min at room temperature.…”
Section: Measurement Parametersmentioning
confidence: 99%
“…In contrast, ASs in LRI are relatively few and distributed irregularly, as reported in the rat [1,14,26], dog [20] and human kidneys [22]. Therefore, we assessed ASs only in the LRE of the GBM in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The glomerular ASs are mainly composed of heparan sulphate proteoglycan (HSPG) which is one of the major constituents of the GBM [10]. Immunohistochemical studies have revealed no diminution in glomerular staining of HSPG in human diabetic glomerulosclerosis [30], human glomerulonephritis [7] and nephrotoxic nephritis in dogs [20]. In contrast, a structural alteration of HSPG has been suggested to explain the loss of charge selectivity resulting in proteinuria [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation